Human Umbilical Cord Blood Serum Has Higher Potential in Inducing Proliferation of Fibroblast than Fetal Bovine Serum - Sandra, Ferry; Lahirin, Rita (Molecular and Cellular Biomedical Sciences, 2017)
Background: Cytokines and growth factors were reported to play an important role in stimulating fibroblast proliferation. In vitro culture, fibroblast is mostly culture in medium containing fetal bovine serum (FBS).  Human umbilical cord blood (hUCB) has been reported to have low immunogenic property and potential in wound healing, so therefore hUCB serum (hUCBS) could be potential and were investigated in current study.Materials and Methods: Five hUCBs were collected from healthy volunteers with normal delivering procedure. hUCB was ex utero immediately collected from umbilical vein in vacutainers and processed. NIH3T3 cells were cultured in DMEM with 10% FBS or 5-20% hUCBS for 48 hours. Cells were then quantified using MTT assay. Protein concentration of FBS and hUCBS were quantified using Bradford assay.Results: NIH3T3 cells density grown in DMEM with 10% FBS was the lowest. NIH3T3 cells densities were increased along with the increment of hUCBS concentrations. MTT results showed that average number of NIH3T3 cells grown in DMEM with 10% FBS was 6,185±1,243. Meanwhile average numbers of NIH3T3 cells grown in DMEM with 5%, 10% and 20% hUCBS were 8,126±628, 9,685±313 and 12,200±304, respectively. Average numbers of NIH3T3 cells grown in DMEM with 5% hUCBS were significantly higher than the ones with 10% FBS (p=0.000). Bradford results showed that concentration of hUCBS was significantly higher than the one of FBS (p=0.000).Conclusion: hUCBS could induce higher proliferation rate of NIH3T3 cells than FBS. Hence hUCBS could be suggested as an alternate of FBS in inducing fibroblast.Keywords: NIH3T3, fibroblast, UCB, serum, FBS, proliferation